2020
DOI: 10.1371/journal.pntd.0008849
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic fingerprinting of Neotropical hard tick species (Acari: Ixodidae) using a self-curated mass spectra reference library

Abstract: Matrix-assisted laser desorption/ionization (MALDI) time-of-flight mass spectrometry is an analytical method that detects macromolecules that can be used for proteomic fingerprinting and taxonomic identification in arthropods. The conventional MALDI approach uses fresh laboratory-reared arthropod specimens to build a reference mass spectra library with high-quality standards required to achieve reliable identification. However, this may not be possible to accomplish in some arthropod groups that are difficult … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The extracted compounds, mainly consisting of small cytosolic proteins and peptides (Ryzhov & Fenselau, 2001), are measured by matrix‐assisted laser desorption ionization time of flight mass spectrometry (MALDI‐TOF MS) producing species‐specific mass spectra, allowing the differentiation and, in combination with a reference database, the identification of specimens. Within the last 10 years several proof‐of‐concept studies on metazoans have revealed its general applicability for invertebrates (Murugaiyan & Roesler, 2017), specifically for insects (Campbell, 2005; Chavy et al, 2019; El Hamzaoui et al, 2018; Hasnaoui et al, 2022; Lawrence et al, 2019) and arachnids (Diarra et al, 2017; Gittens et al, 2020; Karger et al, 2019; Ngoy et al, 2021), which are relevant as vectors and pests. Far fewer studies have addressed taxa less relevant to human health.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted compounds, mainly consisting of small cytosolic proteins and peptides (Ryzhov & Fenselau, 2001), are measured by matrix‐assisted laser desorption ionization time of flight mass spectrometry (MALDI‐TOF MS) producing species‐specific mass spectra, allowing the differentiation and, in combination with a reference database, the identification of specimens. Within the last 10 years several proof‐of‐concept studies on metazoans have revealed its general applicability for invertebrates (Murugaiyan & Roesler, 2017), specifically for insects (Campbell, 2005; Chavy et al, 2019; El Hamzaoui et al, 2018; Hasnaoui et al, 2022; Lawrence et al, 2019) and arachnids (Diarra et al, 2017; Gittens et al, 2020; Karger et al, 2019; Ngoy et al, 2021), which are relevant as vectors and pests. Far fewer studies have addressed taxa less relevant to human health.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, MALDI‐TOF MS appears as a robust method for accurate molecular identification and entomological surveillance (Yssouf et al ., 2016; Rakotonirina et al ., 2020). This approach has been successfully applied for some groups of disease vectors (Kaufmann et al ., 2011; Yssouf et al ., 2013a, 2014; Mewara et al ., 2018; Zurita et al ., 2019; dos Santos Souza et al ., 2020; Gittens et al ., 2020; Ouarti et al ., 2020; Rot et al ., 2020), for discriminating species complexes and cryptic species (Kaufmann et al ., 2012; Müller et al ., 2013; Yssouf et al ., 2013b). Some studies have applied this method for phlebotomine sand fly research (Dvořák et al ., 2014, 2020; Mathis et al ., 2015; Lafri et al ., 2016; Halada et al ., 2018a, 2018b; Arfuso et al ., 2019) and few ones have focused on New World phlebotomine sand flies (Mathis et al ., 2015; Chavy et al ., 2019).…”
Section: Detecting Cryptic Speciesmentioning
confidence: 99%
“…The extracted compounds, mainly consisting of small cytosolic proteins and peptides (Ryzhov & Fenselau, 2001) are measured by matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) producing species-specific mass spectra, allowing the differentiation and, in combination with a reference database, the identification of specimens. Within the last ten years several proof-of-concept studies on metazoans revealed its general applicability for invertebrates (Murugaiyan & Roesler, 2017), specifically for insects (El Hamzaoui et al, 2018, Chavy et al, 2019, Lawrance et al, 2019, Hasnaoui et al, 2022 and arachnids (Diarra et al, 2017, Karger et al, 2019, Gittens et al, 2020, Ngoy et al, 2021, which are relevant as vectors and pests. Far less studies address taxa less relevant to human health.…”
Section: Introductionmentioning
confidence: 99%